Prolonged Glucocorticoid Treatment in ARDS: Impact on Intensive Care Unit-Acquired Weakness - Meduri, Gianfranco Umberto; Schwingshackl, Andreas; Hermans, Greet (Frontiers in Pediatrics, 2016)
Abstract Systemic inflammation and duration of immobilization are strong independent risk factors for development of intensive care unit- acquired weakness (ICUAW). Activation of the pro-inflammatory transcription factor nuclear factor-κB (NF-κB) results in muscle wasting during disuse-induced skeletal muscle atrophy (ICU bed rest) and septic shock. In addition, NF-κB-mediated signaling plays a significant role in mechanical ventilation-induced diaphragmatic atrophy and contractile dysfunction. Older trials investigating high dose glucocorticoid treatment reported a lack of a sustained anti-inflammatory effects and an association with ICUAW. However, prolonged low-to-moderate dose glucocorticoid treatment of sepsis and ARDS is associated with a reduction in NF-κB DNA-binding, decreased transcription of inflammatory cytokines, enhanced resolution of systemic and pulmonary inflammation, leading to fewer days of mechanical ventilation, and lower mortality. Importantly, meta-analyses of a large number of randomized controlled trials (RCTs) investigating low-to-moderate glucocorticoid treatment in severe sepsis and ARDS found no increase in ICUAW. Furthermore, while the ARDS network trial investigating methylprednisolone treatment in persistent ARDS is frequently cited to support an association with ICUAW, a re-analysis of the data showed a similar incidence with the control group. Our review concludes that in patients with sepsis and ARDS any potential direct harmful neuromuscular effect of glucocorticoids appears outweighed by the overall clinical improvement and reduced duration of organ failure, in particular ventilator dependency and associated immobilization, which are key risk factors for ICUAW. Acknowledgements: The NHLBI ARDSnetwork graciously provided and assisted with the ARDSnet02 Dataset on the “Efficacy of Corticosteroids as Rescue Therapy for the Late Phase of Acute Respiratory Distress Syndrome (LaSRS)”.